2021
DOI: 10.3390/molecules26237094
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Nano-Liquid Chromatography and Dispersive Liquid-Liquid Microextraction Applied to the Analysis of Antifungal Drugs in Milk

Abstract: A novel chromatographic application in chiral separation by using the nano-LC technique is here reported. The chiral recognition of 12 antifungal drugs was obtained through a 75 µm I.D. fused-silica capillary, which was packed with a CSP-cellulose 3,5-dichlorophenylcarbamate (CDCPC), by means of a lab-made slurry packing procedure. The mobile phase composition and the experimental conditions were optimized in order to find the optimum chiral separation for some selected racemic mixtures of imidazole and triazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…An essential aspect of the mobile phase composition study is the change of the organic, water, and additive content to enhance specific CSP‐analyte interactions, especially enantioselective ones. In our previous chiral studies, it has been reported that changing the composition of binary mobile ACN/water, MeOH/water [22], and MeOH/ACN [18] had a significant effect on the analytes’ k′ 1 and Rs .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An essential aspect of the mobile phase composition study is the change of the organic, water, and additive content to enhance specific CSP‐analyte interactions, especially enantioselective ones. In our previous chiral studies, it has been reported that changing the composition of binary mobile ACN/water, MeOH/water [22], and MeOH/ACN [18] had a significant effect on the analytes’ k′ 1 and Rs .…”
Section: Resultsmentioning
confidence: 99%
“…All nano‐LC analyses were carried out employing a semi‐laboratory‐assembled instrumentation previously reported by our group [18]. The CSP was polysaccharide‐based, where 20% (w/w) AMY–3Cl–5Me) as chiral selector was covalently immobilized on native silica (nominal particle size and pore size, 5 µm and 1000 Å, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diverse CSs have been employed to separate enantiomers from various kinds of chemicals. Peptides, proteins, chiral AAs, CDs or their derivatives, polysaccharides (modified amylose and cellulose), glycopeptide antibiotics, chiral surfactants, chiral crown-ethers, and other CS are among the most often used [17,21,[39][40][41][42]. A brief review of the key CSs in nano-LC/CLC is provided below.…”
Section: Nano-lc Approaches To Enantiomer Resolutionmentioning
confidence: 99%